Murder at Sunrise Lake - Feehan, Christine (Berkley, 2021)
"#1 New York Times bestselling author Christine Feehan reaches new heights of passion and suspense in this thrilling novel that takes readers deep into the California backcountry, where a woman is tormented by visions of a killer. It starts in her dreams. Hideous flashes from a nightmare only she can stop. Images of a murderer stalking the ones she cares about most. . . . Stella Harrison thought she had gotten away from the traumas of her past. Running the Sunrise Lake Resort high in the Sierra Nevada mountains has brought her peace, even though she doesn't truly share her quiet life with anyone. Not even Sam, the hired handyman who notices everything and always seems to know exactly what she needs. Stella doesn't know anything about Sam's past, but somehow over the last two years his slow, steady presence has slipped past her defenses. Still, she knows she can't tell him about her recent premonitions. So far there's been no murder. No body. No way to prove what is about to happen without destroying the life she has built for herself. But a killer is out there. And Stella knows that this time she'll do whatever it takes to stop him"--